(untitled) (Journal of The Colloquium for Information Systems Security Education, 2025)
The cybersecurity industry faces a persistent shortage of skilled professionals, as employers report significant challenges in hiring qualified candidates. This study examines the specific technical and non-technical skills that employers find most lacking in new hires and evaluates the importance of practical experience in workforce readiness. Through a survey of 200 senior cybersecurity leaders, we assess which skills are most valued, which are most frequently lacking, and how employer satisfaction varies by education model. The findings indicate that while hands-on experiences, such as real-world projects and capstone work, are linked to higher satisfaction, traditional training programs — including university and boot camp models—show no statistically significant difference in employer satisfaction. Notably, the hiring challenges noted by employers are not fully explained by NICE-aligned technical competencies, underscoring the need for better alignment between training expectations and industry demands. These results emphasize the value of contextualized, practical experience rather than reliance on predefined skill taxonomies.